2018
DOI: 10.1111/pbi.13034
|View full text |Cite
|
Sign up to set email alerts
|

A new genomic tool for walnut (Juglans regia L.): development and validation of the high‐density Axiom™ J. regia 700K SNP genotyping array

Abstract: Summary Over the last 20 years, global production of Persian walnut ( Juglans regia L.) has grown enormously, likely reflecting increased consumption due to its numerous benefits to human health. However, advances in genome‐wide association ( GWA ) studies and genomic selection ( GS ) for agronomically important traits in walnut remain limited due to the lack of powerful genomic tools. Here, we present the development and validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 45 publications
9
83
0
Order By: Relevance
“…636 This was evident in the different percent heterozygous estimate of the fixed probes in the 637 between laboratory replicate extractions (Table S10). However, our technical error is similar to 638 previous genotype concordance estimates ranging from 0.2% to 2.4% for replicates of a given 639 subject genotyped on Affymetrix SNP arrays for humans (Hong et al 2012), rainbow trout (Palti 640 et al 2015), soybean (Lee et al 2015) and walnut (Marrano et al 2019). In that latter study, the 641 variation was also higher between technical replicates than biological replicates, which the 642 authors attributed to DNA quality.…”
Section: Discussion 611supporting
confidence: 79%
“…636 This was evident in the different percent heterozygous estimate of the fixed probes in the 637 between laboratory replicate extractions (Table S10). However, our technical error is similar to 638 previous genotype concordance estimates ranging from 0.2% to 2.4% for replicates of a given 639 subject genotyped on Affymetrix SNP arrays for humans (Hong et al 2012), rainbow trout (Palti 640 et al 2015), soybean (Lee et al 2015) and walnut (Marrano et al 2019). In that latter study, the 641 variation was also higher between technical replicates than biological replicates, which the 642 authors attributed to DNA quality.…”
Section: Discussion 611supporting
confidence: 79%
“…Serr (JrSerr_v1.0; 534.7 Mb) (Zhu et al 2019) can be explained by structural variation (e.g., copy number and presence/absence variants), whose central role in explaining intraspecific genomic and phenotypic diversity has been reported in different plant species (Springer et al 2009; Marroni et al 2014). In addition, the higher number of unanchored scaffolds in Chandler v2.0 compared to JrSerr_v1.0 can represent autozygous genomic regions of Chandler, devoid of segregating markers and, therefore, difficult to anchor to linkage genetic maps (Luo et al 2015), as also suggested by the higher fixation index ( F ) observed in Chandler (0.03) than Serr (-0.29) in previous genetic surveys (Marrano et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In these nine low heterozygous regions, we found 1,536 SNPs in total ( Figure 2 ), of which only 25 were tiled on the Axiom J. regia 700K SNPs array. The absence of these polymorphisms segregating in Chandler in the SNP array could be related to either a failed identification during the SNP calling due to the highly fragmented reference genome v1.0 or with the SNP exclusion during the filtering process applied to build the genotyping array (Marrano et al 2018). The low number of Chandler heterozygous SNPs in the array affected the end of Chr15 the most, causing a reduction in the genetic length of the corresponding linkage group ( Figure 1 ), as well as leaving unexplored 4 Mb of Chandler genetic variability, which is now accessible thanks to the new chromosome-scale reference genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations